2001
DOI: 10.1073/pnas.191353898
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cyclin-dependent kinase 5 and casein kinase 1 by metabotropic glutamate receptors

Abstract: Cyclin-dependent kinase 5 (Cdk5) is a multifunctional neuronal protein kinase that is required for neurite outgrowth and cortical lamination and that plays an important role in dopaminergic signaling in the neostriatum through phosphorylation of Thr-75 of DARPP-32 (dopamine and cAMP-regulated phosphoprotein, molecular mass 32 kDa). Casein kinase 1 (CK1) has been implicated in a variety of cellular functions such as DNA repair, circadian rhythm, and intracellular trafficking. In the neostriatum, CK1 has been fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
129
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 119 publications
(137 citation statements)
references
References 45 publications
(51 reference statements)
8
129
0
Order By: Relevance
“…The p35/cdk5 complex was immunoprecipitated from the supernatant by using a specific cdk5 antibody. Cdk5 activity assays were performed as described previously (44). Proteins were separated by SDS/PAGE, and data were quantified by using a PhosphorImager (Molecular Dynamics, Sunnyvale, CA).…”
Section: Primary Neuronal and Cos-7 Cell Cultures And Incubation Withmentioning
confidence: 99%
“…The p35/cdk5 complex was immunoprecipitated from the supernatant by using a specific cdk5 antibody. Cdk5 activity assays were performed as described previously (44). Proteins were separated by SDS/PAGE, and data were quantified by using a PhosphorImager (Molecular Dynamics, Sunnyvale, CA).…”
Section: Primary Neuronal and Cos-7 Cell Cultures And Incubation Withmentioning
confidence: 99%
“…We have recently reported that, by activating casein kinase 1 (CK1) in a PLC-dependent manner, group I mGlu receptors cause an increase in the phosphorylation of DARPP-32 at Ser-137 (17,18). Moreover, by activating cyclin-dependent kinase 5 (Cdk5), this activation of CK1 causes an increase in the phosphorylation of DARPP-32 at Thr-75 (17).…”
Section: Activation Of Intracellular Signaling By Mglu5 Receptors Invmentioning
confidence: 99%
“…Equal amounts of protein were processed by using 10% acrylamide gels as described (17). Immunoblotting was carried out with phosphorylation-state-specific antibodies against phospho-Thr-34-DARPP-32 (18), phospho-Thr-75-DARPP-32 (9), phospho-Ser-137-DARPP-32 (19), phospho-Ser-831-GluR1 (Upstate Biotechnology, Lake Placid, NY), phospho-Ser-845-GluR1 (Upstate Biotechnology), or antibodies that are not phosphorylation-state-specific against total DARPP-32 (20) and total GluR1 (Upstate Biotechnology). Antibody binding was detected by enhanced chemiluminescence (ECL; Amersham Pharmacia) and quantified by densitometry, using National Institutes of Health IMAGE 1.61 software.…”
Section: Preparation and Treatment Of Slices From Hippocampus Prefromentioning
confidence: 99%